Radiation measurements from polar and geosynchronous satellites - Vonder Haar, T. H., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1974)
Annual report for National Aeronautics and Space Administration grant NGR-06-002-102 for period: 1 October 1972-30 September 1973.
February, 1974.
Keywords: Solar radiation -- Measurement; Satellite meteorology; Atmospheric radiation -- Remote sensing